Prognostic value of pathologic fracture in patients with high grade localized osteosarcoma: A systemic review and meta‐analysis of cohort studies. Issue 1 (18th September 2014) - Sun, Lingling; Li, Yingiun; Zhang, Jian; Li, Hengyuan; Li, Binghao; Ye, Zhaoming
ABSTRACT Consensus has not been reached regarding the ability of pathologic fracture to predict local recurrence and survival in osteosarcoma. We aim to review the available evidence to examine the association between pathologic fracture and osteosarcoma prognosis. A comprehensive literature search for relevant studies published until March 2014 was performed using PubMed, Cochrane and Web of Science. The studies investigating pathologic fracture of osteosarcoma patients were systematically analyzed. The overall relative risk (RR) was estimated using a fixed‐effect model or random‐effect model according to heterogeneity between the trials. We included nine cohort studies involving 2, 187 patients (311 with pathologic fracture and 1, 876 without fracture) for the analysis of survival rate and local recurrence. Studies were assessed for quality using the Newcastle–Ottawa Assessment Scale. In the fixed‐effects model, the meta‐analysis showed that pathologic fracture in osteosarcoma patients predicted poor 3‐year overall survival (OS) (RR = 1.86, 95% CI: 1.37–2.53, p < 0.001) and 5‐year OS (RR = 1.34, 95% CI: 1.06–1.70, p = 0.016). Similarly, pathologic fracture was significantly correlated with worse 3‐year event free survival (EFS) (RR = 1.52, 95% CI: 1.21–1.92, p < 0.001) and 5‐year EFS (RR = 1.24, 95% CI: 1.03–1.49, p = 0.021), whereas no significant association was noted with local recurrence (RR = 1.30, 95% CI: 0.84–2.02, p = 0.233). The meta‐analysis confirmed that pathologic fracture in osteosarcoma was a prognostic marker for both OS and EFS but not for local recurrence. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:131–139, 2015.